A three-dimensional porous Co@C/carbon foam hybrid monolith for exceptional oil–water separation. Issue 25 (14th June 2019) - Ge, Xiao; Qin, Wenxiu; Zhang, Haimin; Wang, Guozhong; Zhang, Yunxia; Yu, Chengzhong
Abstract : A 3D porous Co@C/CF hybrid monolith and the corresponding oil-collecting device have been successfully fabricated for exceptional oil/water separation. Abstract : Frequent oil spill accidents and ever-increasing oily wastewater have become serious global environmental problems. To enhance the oil-sorption capacity and simplify the oil-recovery process, the construction of various advanced oil sorbents and oil-collecting devices is of great technological importance. Herein, a three-dimensional (3D) porous carbon-based hybrid monolith has been successfully fabricated, in which cobalt based metal–organic framework (Co-MOF) nanosheets are firstly immobilized on a carbon foam (CF) skeleton (denoted as Co-MOFs/CF) via a facile vapor-phase hydrothermal (VPH) technique followed by carbonation treatment under a N2 atmosphere into Co@C/CF. The resulting Co@C/CF hybrid monolith exhibits an exceptional oil/water separation ability, including high sorption capacity (from 85 to 200 times its own weight toward various solvents and oils), easy collection and remarkable recyclability, as reflected by no obvious reduction in uptake capacity even after 20 cycles of repeated operation. More significantly, the oil-collecting device based on the proposed carbon-based hybrid monolith can rapidly, efficiently, and continuously collect oil from water surfaces, making it a promising candidate for oil-spill remediation.